Role of sortase in Streptococcus mutans under the effect of nicotine - Li, Ming-Yun (Nature Publishing Group, 2013)
Streptococcus mutans is a common Gram-positive bacterium and plays a significant role in dental caries. Tobacco and/or nicotine have documented effects on S. mutans growth and colonization. Sortase A is used by many Gram-positive bacteria, including S. mutans, to facilitate the insertion of certain cell surface proteins, containing an LPXTGX motif such as antigen I/II. This study examined the effect of nicotine on the function of sortase A to control the physiology and growth of S. mutans using wild-type S. mutans NG8, and its isogenic sortase-defective and -complemented strains. Briefly, the strains were treated with increasing amounts of nicotine in planktonic growth, biofilm metabolism, and sucrose-induced and saliva-induced antigen I/II-dependent biofilm formation assays. The strains exhibited no significant differences with different concentrations of nicotine in planktonic growth assays. However, they had significantly increased (P≤0.05) biofilm metabolic activity (2- to 3-fold increase) as the concentration of nicotine increased. Furthermore, the sortase-defective strain was more sensitive metabolically to nicotine than the wild-type or sortase-complemented strains. All strains had significantly increased sucrose-induced biofilm formation (2- to 3-fold increase) as a result of increasing concentrations of nicotine. However, the sortase-defective strain was not able to make as much sucrose- and saliva-induced biofilm as the wild-type NG8 did with increasing nicotine concentrations. These results indicated that nicotine increased metabolic activity and sucrose-induced biofilm formation. The saliva-induced biofilm formation assay and qPCR data suggested that antigen I/II was upregulated with nicotine but biofilm was not able to be formed as much as wild-type NG8 without functional sortase A.